All about flooble | fun stuff | Get a free chatterbox | Free JavaScript | Avatars    
perplexus dot info

Home > Just Math
Rational Rubric (Posted on 2015-03-01) Difficulty: 2 of 5
Prove that the only rational solution to the equation:
A3 + 3*B3 + 9*C3 = 3*A*B*C
is A=B=C=0

No Solution Yet Submitted by K Sengupta    
Rating: 4.0000 (1 votes)

Comments: ( Back to comment list | You must be logged in to post comments.)
Solution q.e.d. (spoiler) | Comment 1 of 2

(0) Assume there is a solution other than A = B = C = 0

(1) Clearly, if two of them are zero, the 3rd must be 0 also.

(2) Further, assume one of them is zero and the other two are not.  Then either (A^3 = -3B^3)  or (A^3 = -9C^3) or (B^3 = -3C^3)

Clearly, none of these have a rational solution, because 3 and 9 have irrational cube roots.  Therefore, we have a contradiction, so assumption (2) is incorrect.

(3) So, we know that A, B and C are all non-zero.  Express them as fractions in lowest terms.

    Multiply A, B and C by the least common multiple (LCM) of their denominators, giving D, E and F.   Now D, E and F are integers.

    Divide D, E and F by their greatest common factor (GCF), giving G, H, and I.   G, H and I are integers without a factor common to all three of them.    

(4) It must the case that G^3 + 3H^3 + 9I^3 = 3GHI.

    But this means that G must be a multiple of 3, because the other terms are all multiples of 3.

    Let G = 3J and substitute.

    Then 27J^3 + 3H^3 + 9I^3 = 9JHI.

    Dividing by 3 gives 9J^3 + H^3 + 3I^3 = 3JHI.

    But this means that H must be a multiple of 3, because the other terms are all multiples of 3.

    Let H = 3K and substitute.

    Then 9J^3 + 27K^3 + 3I^3 = 9JKI.

    Dividing by 3, 3J^3 + 9K^3 + I^3 = 3JKI.

    Now I must be a multiple of 3, because the other terms are all multiples of 3.    

 (5) And at this point, we have reached a contradiction.  G, H and I are all multiples of 3.  But this is impossible, because we got them by dividing D, E and F by their greatest common factor.

Therefore, assumption (0) is false.  The only solution is A = B = C = 0.

q.e.d. 


  Posted by Steve Herman on 2015-03-01 13:42:28
Please log in:
Login:
Password:
Remember me:
Sign up! | Forgot password


Search:
Search body:
Forums (0)
Newest Problems
Random Problem
FAQ | About This Site
Site Statistics
New Comments (4)
Unsolved Problems
Top Rated Problems
This month's top
Most Commented On

Chatterbox:
Copyright © 2002 - 2017 by Animus Pactum Consulting. All rights reserved. Privacy Information